2018
DOI: 10.1039/c7mt00334j
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of copper transporter 1 and organic cation transporters 1–3 for oxaliplatin uptake and drug resistance in colorectal cancer cells

Abstract: Oxaliplatin is a routinely used drug in the treatment of colorectal cancer. However, development of resistance is a major hurdle of the chemotherapy success. Defects in cellular accumulation represent a frequently reported feature of cells with acquired resistance to platinum drugs. Nevertheless, the mechanisms of oxaliplatin uptake and their role in oxaliplatin resistance remain poorly elucidated. The aim of this study was to investigate the relevance of copper transporter 1 (CTR1) and organic cation transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Another important issue that should be addressed in further research is how the uptake of the drugs is regulated and by which cellular pathway. For the uptake of platinum-based drugs, the copper transporter-1 (CTR-1) and the organic cation transporter 1-3 (OCT1-3) have been described to be important [60,61]. Cui et al demonstrated that different human CRC cell lines express high levels of CTR-1 protein in similar localization patterns, despite the different sensitivity to oxaliplatin [60].…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue that should be addressed in further research is how the uptake of the drugs is regulated and by which cellular pathway. For the uptake of platinum-based drugs, the copper transporter-1 (CTR-1) and the organic cation transporter 1-3 (OCT1-3) have been described to be important [60,61]. Cui et al demonstrated that different human CRC cell lines express high levels of CTR-1 protein in similar localization patterns, despite the different sensitivity to oxaliplatin [60].…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al reported that omeprazole could decrease the protein level of OCT2, thus lead to reduced cellular accumulation of cisplatin . Buss et al (2018) employed a novel fluorescent oxaliplatin FIGURE 2 | A schematic of the mechanisms affecting platinum response. The response toward platinum-based antitumor agents can result from (a) cellular drug accumulation.…”
Section: Solute Carrier Superfamily Of Membrane Transportersmentioning
confidence: 99%
“…Coincubation with 200 μ m CuSO 4 , which will saturate the copper transporter CTR1, does not alter the cellular accumulation of any of the complexes (Figure D), suggesting that they are not being taken up by this pathway. This result is in contrast to that for the platinum‐based anticancer drugs, whose uptake is correlated to CTR1 expression levels . Incubation with the organic cation transporter (OCT) inhibitor procainamide significantly reduced the cellular uptake levels of Ru265 and Ru265′, but not Ru360′ (Figure E).…”
Section: Resultsmentioning
confidence: 70%
“…The organic cation transporters OCT1, OCT2, and OCT3 are primarily responsible for the transport of signaling molecules and metabolites such as dopamine, serotonin, and choline. However, these transporters have recently been shown to mediate the uptake of several cationic monofunctional platinum(II) anticancer complexes, suggesting that they may have a more general affinity for coordination complexes.…”
Section: Resultsmentioning
confidence: 99%